2015
DOI: 10.1007/s12253-015-9925-8
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytosis of Liver Metastasis from Colorectal Cancer as Predictive Factor

Abstract: There is increasing evidence that thrombocytosis is associated with tumor invasion and metastasis formation. It was shown in several solid tumor types that thrombocytosis prognosticates cancer progression. The aim of this study was to evaluate preoperative thrombocytosis as a potential prognostic biomarker in isolated metastases, in patients with liver metastasis of colorectal cancer (mCRC). Clinicopathological data of 166 patients with mCRC who had surgical resection between 2001 and 2011 were collected retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 50 publications
0
9
0
1
Order By: Relevance
“…of note, we used a randomeffects model in the presence of heterogeneity (i 2 =66.5%, p<0.001). The studies proposing a strong poor prognostic role of thrombocytosis in cRc included those of cravioto-Villanueva et al (43), Kaneko et al (20), Jósa et al (45), and Toiyama et al (21). For DFs, a greater HR was observed in our study cohort (HR=1.96, 95% ci=1.23-2.69) with a random-effects model (i 2 =69.3%, p=0.002).…”
Section: Meta-analysismentioning
confidence: 46%
“…of note, we used a randomeffects model in the presence of heterogeneity (i 2 =66.5%, p<0.001). The studies proposing a strong poor prognostic role of thrombocytosis in cRc included those of cravioto-Villanueva et al (43), Kaneko et al (20), Jósa et al (45), and Toiyama et al (21). For DFs, a greater HR was observed in our study cohort (HR=1.96, 95% ci=1.23-2.69) with a random-effects model (i 2 =69.3%, p=0.002).…”
Section: Meta-analysismentioning
confidence: 46%
“…Finally, this meta-analysis included 9 retrospective cohort studies comprising 3413 patients with colorectal cancer. [ 5 , 10 , 15 , 24 29 ]…”
Section: Resultsmentioning
confidence: 99%
“…Early in 1998, Monreal M et al reported a significant association between pre-operative platelet count and survival in patients with colorectal cancer. The following studies confirmed this association [2, 3, 5, 6]. However, some other studies failed to demonstrate the association between pretreatment elevated platelet count and outcomes of colorectal cancer [1116].…”
Section: Introductionmentioning
confidence: 87%